Tennis psychology: An overview and update - Crespo, M. (2000)
Overview about the main psychological and mental factors in tennis and the research which is done in this field. Main factors are anticipation, motivation, visualization, attention, anxiety, stress, concentration. Other important factors are psychological routines and mental training, personality and gender, motor learning or the parents of the players.